1988
DOI: 10.1161/01.hyp.12.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-diuresis in volume-expanded rats. Tubular reabsorption in superficial and deep nephrons.

Abstract: SUMMARY Micropuncture experiments were performed in volume-expanded rats to better define the nephron segments in which changes in renal perfusion pressure inhibit tubular reabsorption. Neural influences on the kidney were eliminated by renal denervation, and plasma levels of vasopressin, aldosterone, cortkosterone, and norepinephrine were maintained at fixed levels by i.v. infusion. Fractional excretion of sodium, chloride, and water increased markedly after renal perfusion pressure was elevated from 110 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 20 publications
2
52
1
Order By: Relevance
“…These studies suggest that the loop of Henle may play a compensatory role during the process of pressure natriuresis. In contrast, Roman 11 reported that alterations in medullary hemodynamics participate in the pressure-natriuretic response by inhibiting tubular reabsorption in the proximal tubule and the thin descending limb of the loop of Henle (or both) of juxtamedullary nephrons. Thus, changes in renal perfusion pressure within the autoregulatory range may elicit changes in tubular sodium reabsorption in multiple nephron segments.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that the loop of Henle may play a compensatory role during the process of pressure natriuresis. In contrast, Roman 11 reported that alterations in medullary hemodynamics participate in the pressure-natriuretic response by inhibiting tubular reabsorption in the proximal tubule and the thin descending limb of the loop of Henle (or both) of juxtamedullary nephrons. Thus, changes in renal perfusion pressure within the autoregulatory range may elicit changes in tubular sodium reabsorption in multiple nephron segments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NO appears to exert a tonic vasodilation of the vasa recta in the renal medulla. Variations in NO synthesis will be followed by proportional changes in renomedullary blood flow and thereby in renal interstitial pressure and will produce an inversely related change in sodium reabsorption (132). We will examine this mechanism later on.…”
Section: Intrarenal Functions Regulated By Ang II and Nomentioning
confidence: 99%
“…A group of investigators at the Medical College of Wisconsin has accumulated a significant amount of evidence showing that, in the rat, the integrity of the renal medullary circulation is very critical in maintaining pressure natriuresis (132). In fact, they found that increments in renal perfusion pressure above 78-85 mmHg produced proportional changes in renal papillary flow, whereas renal cortical flow does not change because it is effectively autoregulated (94).…”
Section: Role Of Oxst On Endothelial Function and On Medullary Circulmentioning
confidence: 99%
“…There is strong evidence that this mechanism is mediated, at least in part, by a direct relationship between renal arterial pressure (RAP) and renal interstitial hydrostatic pressure, which in turn profoundly influences tubular sodium reabsorption (13,25,34,35). However, there is still much controversy as to the mechanism(s) by which increased RAP increases renal interstitial hydrostatic pressure, because total renal blood flow (RBF) and glomerular filtration rate are well autoregulated.…”
mentioning
confidence: 99%